Rancang Bangun Sistem Pendeteksi Kebakaran Lahan Gambut Jenis Kayuan Dengan Memanfaatkan Karakteristik Panas Yang Ditimbulkannya - Gilang Bagaskara; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Peatland fires monitoring that have the highest accuracy is ASMC with an accuracy rate of 60%. So it takes a peat fire detection design, in order to mitigate catastrophic fires in peatlands. Peat in Riau province generally woody peat types, so that the research done on woody peat. This detection system utilizing the characteristics of the heat generated by peat fires trees is LM35 sensor, using ATMega8 as the microcontroller and LCD 16*2 as the viewer that read the temperature sensor. Based on these results, LM35 temperature sensor has an accuracy rate with an %error on the average of o.22% to the lowest %error is 0% and the %error is 0.62% higher. The temperature of woody peat area in normal condition at 08.00 to 11.30 pm has a large temperature that always under ambient temperature. When burning conditions, the temperature of woody peat area continues to increase and exceeds ambient temperature. There is no significant difference of the air temperature around the area when normal conditions and during a fire because woody peat fires not really affect the change.Keywords: LM35 Sensor, ATMega8, woody peat